Análisis de la expresión de los genes chr de Burkholderia xenovorans LB400 - Luna Luna, Maurino (Universidad Michoacana de San Nicolás de Hidalgo, 2010)
Microorganisms that contain more than one homolog of The CHR chromate transport superfamily. Among these is the bacterium Gram (-) Burkholderia xenovorans LB400, with two SCHR homologues (Chr1NCa and Chr1NCb) and four LCHR homologues (ChrA1a, ChrA1b, ChrA2 and ChrA6). Recently In our working group, four CHR homologues of B. xenovorans, three From the LCHR family and one from the SCHR family. These homologues were found to confer Chromate resistance when expressed in Escherichia coli, although in different Culture conditions the objective of this work was to determine the expression pattern of Genes encoding CHR homologs. For this purpose RT-PCR assays are used From the total RNA of B. xenovorans cells grown in nutrient broth (CN), medium Minimum M9 with high (2 mM) and low (0.04 mM) sulfate concentration. When the Cultures were grown in CN, an exception of the chrA6 gene, which was not expressed, the other genes they showed expression signal and for most cases increased in the presence of chromate. When the cultures were grown in high sulfate to the log phase of growth, all genes were expressed and also responded to chromate exposure. Alabama As in the log phase, in the stationary phase all the genes showed expression, without However, in this condition the chr1NCa genes did not show an increase in their expression By the addition of chromate. Under low sulfate conditions, an exception of chrA6 that is not He expressed, in both phases of growth, all the chr genes showed an increase in their Expression level with respect to high sulphate and chromium trials led to changes Null or moderate in expression.

Se han identificado microorganismos que en su genoma contienen más de un homólogo de la superfamilia de transportadores de cromato CHR. Entre estos se encuentra la bacteria Gram (-) Burkholderia xenovorans LB400, con dos homólogos SCHR (Chr1NCa y Chr1NCb) y cuatro homólogos LCHR (ChrA1a, ChrA1b, ChrA2 y ChrA6). Recientemente en nuestro grupo de trabajo se han estudiado cuatro homólogos CHR de B. xenovorans, tres de la familia LCHR y uno de la familia SCHR. Se encontró que estos homólogos confieren resistencia a cromato cuando se expresan en Escherichia coli, aunque en diferentes condiciones de cultivo. El objetivo de este trabajo fue determinar el patrón de expresión de los genes que codifican los homólogos CHR. Para ello se utilizaron ensayos de RT-PCR a partir de RNA total de células de B. xenovorans crecidas en caldo nutritivo (CN), medio mínimo M9 con alta (2 mM) y baja (0.04 mM) concentración de sulfato. Cuando los cultivos se crecieron en CN, a excepción del gen chrA6, que no se expresó, los demás genes mostraron señal de expresión y para la mayoría ésta aumentó en presencia de cromato. Cuando los cultivos se crecieron en alto sulfato hasta la fase logarítmica de crecimiento, todos los genes chr se expresaron y además respondieron a la exposición de cromato. Al igual que en fase logarítmica, en fase estacionaria todos los genes mostraron expresión, sin embargo, en esta condición los genes chr1NCa no presentaron un aumento en su expresión por la adición de cromato. En condiciones de bajo sulfato, a excepción de chrA6 que no se expresó, en ambas fases de crecimiento todos los genes chr mostraron un aumento en su nivel de expresión con respecto a los ensayos en alto sulfato y el cromato provocó cambios nulos o moderados en la expresión.
Instituto de Investigaciones Químico Biológicas. Maestría en Ciencias en Biología Experimental
Keywords: info:eu-repo/classification/cti/6; IIQB-M-2010-0009; Gen; Familia SCHR; Cromo; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/3860